The burden of severe asthma in childhood and adolescence: results from the paediatric U-BIOPRED cohorts - Fleming, Louise; Murray, Clare; Bansal, Aruna T.; Hashimoto, Simone; Bisgaard, Hans; Bush, Andrew; Frey, Urs; Hedlin, Gunilla; Singer, Florian; Aalderen, Wim M. van; Vissing, Nadja H.; Zolkipli, Zaraquiza; et al. (European Respiratory Society, 2015)
U-BIOPRED aims to characterise paediatric and adult severe asthma using conventional and innovative systems biology approaches.